2014
DOI: 10.1002/ab.21554
|View full text |Cite
|
Sign up to set email alerts
|

Personality Assessment Inventory internalizing and externalizing structure in veterans with posttraumatic stress disorder: Associations with aggression

Abstract: Posttraumatic stress disorder (PTSD) is associated with aggressive behavior in veterans, and difficulty controlling aggressive urges has been identified as a primary postdeployment readjustment concern. Yet only a fraction of veterans with PTSD commit violent acts. The goals of this study were to (1) examine the higher-order factor structure of Personality Assessment Inventory (PAI) scales in a sample of U.S. military veterans seeking treatment for PTSD; and (2) to evaluate the incremental validity of higher-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 92 publications
3
7
0
Order By: Relevance
“…Convergent and discriminant validity has been established with various psychometric instruments relating to constructs assessed by all the scales (Morey, 1996). Subsequent research has confirmed good internal consistency in samples of veterans with PTSD (Van Voorhees et al, 2014), extratest validity in inpatient substance abuse settings (Hopwood, Baker, & Morey, 2008), convergent validity in a federal inmate sample (Patry & Magaletta, 2014), and reliability and consistent factor structure in a neuropsychological sample (Busse, Whiteside, Waters, Hellings, & Ji, 2014). The internal consistency in the present sample ranged from moderate to strong for all scales (α = .69 to α = .95).…”
Section: Methodssupporting
confidence: 64%
See 2 more Smart Citations
“…Convergent and discriminant validity has been established with various psychometric instruments relating to constructs assessed by all the scales (Morey, 1996). Subsequent research has confirmed good internal consistency in samples of veterans with PTSD (Van Voorhees et al, 2014), extratest validity in inpatient substance abuse settings (Hopwood, Baker, & Morey, 2008), convergent validity in a federal inmate sample (Patry & Magaletta, 2014), and reliability and consistent factor structure in a neuropsychological sample (Busse, Whiteside, Waters, Hellings, & Ji, 2014). The internal consistency in the present sample ranged from moderate to strong for all scales (α = .69 to α = .95).…”
Section: Methodssupporting
confidence: 64%
“…As in other veteran samples, the full AGG scale T score for the PTSD group was in the moderate-high range (≥ 65T). Calhoun et al, 2010;Crawford, Calhoun, Braxton, & Beckham, 2007;Mozley et al, 2005;Van Voorhees et al, 2014), whereas civilian samples have consistently shown mean scores below 60T for PTSD groups. This differential elevation in the AGG scale between veteran and nonveteran samples suggests that this PAI scale may have clinical utility in detecting concomitant difficulties with aggression among individuals with PTSD, which is important in light of research indicating that anger and aggression are frequent problems experienced by veterans with PTSD (Calhoun et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, a total measure of the count of violent acts (i.e., minor and severe violence) committed in the past year was scored by assigning the mid-points of the latter four response categories and summing the items (Straus, 1979). Following previous research using the CTS with veterans (Crawford et al, 2007; Jordan et al, 1992; Van Voorhees et al, 2014), high violence was defined as 13 or more violent acts in the past year. Internal consistency of these scoring methods is adequate [alpha .79-.83; (Straus, 1979, 1990)].…”
Section: Methodsmentioning
confidence: 99%
“…We found significant correlations between number of attacks in the resident-intruder test and relative gene expression of TNF (p=0.0065, r=0.478), IL-1β (p=0.0003, r=0.608), GSK-3β (p<0.0001, r=0.692), IL6 (p=0.0059, r=0.483) and number of Ki67-positive cells (p=0.047, r=-0.327, Fig.9.A-E). neurodegenerative (Levenson et al, 2014) conditions, as well as depression (Knox et al, 2000) and stress-related disorders (Van Voorhees et al,2014). Aggressive behaviour during major depression is associated with an enhanced risk of suicide (Gvion & Apter, 2011).…”
Section: Correlations Between Number Of Attacks and Altered Hippocampmentioning
confidence: 99%